RETRACTED: Discrete and analog evaluation of the capillary-pore space of foam concrete in eco-friendly production - Kulikov Vladimir (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001